Fabrication of DNA/RNA templated conductive metal wires for DYE-sensitized solar cell applications / Sehar Shakir - Sehar , Shakir (2018)
In this work, fabrication of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) templated metal wires on substrates were presented and their use as modified counter electrode (CE) in dye sensitized solar cells (DSSCs) has been studied. This research demonstrates a novel and controllable scribing method to fabricate DNA/RNA templated submicron to nanoscale metal wires employing natural capillary force action and the coffee-ring effect. Cyclic voltammetry (CV) measurements showed that DNA/RNA templated metal wires on Si, ITO and Platinum (Pt)/ITO substrates exhibited higher electro-catalytic activity with improved conductivity than conventional Pt/ITO CEs due to the synergistic effect of Pt and metal wire network on ITO. DSSCs designed using TiO2 photoanode, N719 dye, I-/I3- electrolyte and modified electrodes show higher power conversion efficiency under AM 1.5, 100 mWcm-2 illumination compared to cells assembled using the same parameter but conventional (Pt/ITO) CE. Moreover, to enhance photoabsorption and electron generation in DSSCs and to develop compatible photoanodes with our modified CEs, TiO2-based photoanodes were developed using aerosol-assisted chemical vapor deposition (AACVD) and electrophoretic deposition (EPD). The effect of magnesium doping in AACVD developed films at various concentrations and surface modification of EPD films using tin (Sn) were analyzed. A detailed morphological and structural analysis of the films developed using AACVD and EPD has been presented. The overall efficiency improvements were observed when the modified CEs and modified photoanodes were used. Various characterization techniques were employed to analyze the fabricated metal wires and deposited TiO2 electrodes including X-ray diffraction for phase purity, crystallinity and crystallite size determination, X-ray photon spectroscopy for determination of valence state of the metal wires, CV for determination of catalytic activity of the CEs, current density-voltage (J-V) characteristics for analyzing the performance of the DSSCs etc. Various DSSCs were formed and the maximum efficiency of 6.68 % was achieved in DSSC fabricated using DNA templated Au wires on Pt/ITO substrates as CE and 2 mol% Mg doped AACVD TiO2 film on ITO as photoanode.